2014
DOI: 10.1371/journal.pone.0105315
|View full text |Cite
|
Sign up to set email alerts
|

The Staurotypus Turtles and Aves Share the Same Origin of Sex Chromosomes but Evolved Different Types of Heterogametic Sex Determination

Abstract: Reptiles have a wide diversity of sex-determining mechanisms and types of sex chromosomes. Turtles exhibit temperature-dependent sex determination and genotypic sex determination, with male heterogametic (XX/XY) and female heterogametic (ZZ/ZW) sex chromosomes. Identification of sex chromosomes in many turtle species and their comparative genomic analysis are of great significance to understand the evolutionary processes of sex determination and sex chromosome differentiation in Testudines. The Mexican giant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 38 publications
(60 reference statements)
6
49
0
Order By: Relevance
“…Such situation was previously reported among the sex chromosomes of Staurotypus turtles (XY; Kawagoshi et al, 2014) Rens et al, 2007). It was suggested that thanks to their gene content, particularly due to the inclusion of genes related to gonad differentiation, some chromosomes are more likely than others to start functioning as sex chromosomes (O'Meally et al, 2012).…”
Section: Identification Of Putative Z-specific Genessupporting
confidence: 51%
See 2 more Smart Citations
“…Such situation was previously reported among the sex chromosomes of Staurotypus turtles (XY; Kawagoshi et al, 2014) Rens et al, 2007). It was suggested that thanks to their gene content, particularly due to the inclusion of genes related to gonad differentiation, some chromosomes are more likely than others to start functioning as sex chromosomes (O'Meally et al, 2012).…”
Section: Identification Of Putative Z-specific Genessupporting
confidence: 51%
“…As far as we know, sex chromosomes of lacertids are not homologous with those of other sauropsid lineages with known gene content, such as advanced snakes (Matsubara et al, 2006;Vicoso et al, 2013), iguanas (see, for example, Alföldi et al, 2011;Rovatsos et al, 2014a-c), geckos (Kawai et al, 2009), turtles (see, for example, Kawagoshi et al, 2012Kawagoshi et al, , 2014 and birds (see, for example, Zhou et al, 2014). The lacertid Z chromosome partially shares gene content with the ancestral therian X, and thus we assume that these sex chromosome systems probably evolved from the same ancestral chromosome (syntenic block).…”
Section: Identification Of Putative Z-specific Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, because genomes may retain inactive copies of the NOR after translocations have occurred, silver staining reveals only a partial view of NOR's evolutionary history. Thus, we also used 18S rDNA FISH (18S-NOR) as previously applied to a few turtle taxa [Kawai et al, 2007;Cleiton and Giuliano-Caetano, 2008;Badenhorst et al, 2013Badenhorst et al, , 2015Kawagoshi et al, 2014] to detect potentially inactive NOR copies that may have passed undetected in some of the turtles previously examined using AgNOR or scNOR techniques. Our 18S FISH data of the 13 target taxa includes the first reports of 18S-NORs for 7 of them (GIN, CSE, SOD, CIN, EMA, COB, and PSU) ( table 1 ).…”
Section: Turtle Nor Evolutionmentioning
confidence: 99%
“…Of these 10 cases, 3 involved microchromosomes and 7 macrochromosomes. Relatively little is known about the molecular content of turtle sex chromosomes, although information is increasing [Kawagoshi et al, 2009[Kawagoshi et al, , 2012[Kawagoshi et al, , 2014Montiel et al 2016]. Molecular cytogenetic data from comparative genome hybridization (CGH) has been used to identify the extent of the male-or female-limited region of the turtle sex chromosomes [Ezaz et al, 2006;Kawai et al, 2007;Martinez et al, 2008;Badenhorst et al, 2013;Montiel et al, 2016] where recombination should be reduced or absent.…”
Section: Evolution Of Turtle Sex Determinationmentioning
confidence: 99%